Initial Investigation of Sulawesi Moor Macaque (Macaca maura) in Tabo-tabo Forest, South Sulawesi - Indonesia. Issue 1 (November 2021) - Maulany, R.I.; Putra, G.T.S.; Nasri, N.; Hamzah, A.S.; Ngakan, P.O.
Abstract: Sulawesi black crested macaque ( Macaca maura ) is one of the seven endemic macaque inhabited Sulawesi Island and is mainly found in the Southern part of Sulawesi. This species is classified as an endangered species by the International Union for Conservation and Nature (IUCN). The aim of this research was 1) to examine the homerange of M. maura and daily activity of the species, 2) to determine tree species used by the species as diet sources and resting trees in Tabo-tabo Forest, Pangkep Regency (South Sulawesi – Indonesia). The home range was measured by connecting coordinate points passed by a moor macaque group in the area for 6 consecutive days. Meanwhile, daily activity of the species was monitored by using scan sampling method for sampled individuals in three observation periods. Direct observation was carried out to identify diet and resting tree species. It was found that the moor macaque group had 22.06 ha width of home range with the total distance around 6.64 km. The daily distance spent by the group was between 0.9-1.5 km or in average was 1.1 km. The highest activities known to be feeding (30.4%) and then followed by moving (25.3%). While resting activities was allocated for 24.7%. The least activities recorded were social activities (19.6%). Tree species used by the group as diet and resting trees were Anthocephalus chinensis and Dracontomelon dao. The tree species known to be a diet tree only were Garcinia nervosa, Arenga pinnata, Flacourtia rukam, Ficus. sp, Eugenia cuminii, Gastonia serratifolia, Mangifera sp., Spondias dulcis, and Muntingia calabura .